Evaluating the Impact of Urban Road Pricing on the Use of Green Transport Modes The Case of Milan - Cornago, Elisabetta (OECD Publishing, 2019)
The purpose of this study is to investigate the effect of congestion pricing on the demand for clean transport modes. To this end, it draws on an empirical analysis of the effect of Milan's congestion charge on the use of bike sharing. The analysis indicates that congestion pricing increases daily bike-sharing use by at least 5% in the short term. Extending the schedule of the congestion charge in the early evening increases bike-sharing use in the affected time window by 12%. The impact of the policy on bike-sharing use mainly occurs through the reduction of road traffic congestion, which makes cycling safer and more pleasant. The findings of the study indicate that policies aiming to reduce car use also have positive repercussions on the uptake of green mobility options. Relying solely on direct incentives for cycling, which often involve infrastructure projects, is likely insufficient to remove barriers to bike use
Keywords: Environment; Italy